Knowledge on Breastfeeding and Breastfeeding Behavior among Working Mothers and Housewives : A Cohort Study - Nurhasmadiar Nandini; Novia Handayani; Djazuly Chalidyanto; Widodo Jatim Pudjirahardjo; Nuzulul Kusuma Putri (Public Health Faculty, Diponegoro University, Semarang, Indonesia, 2019)
Background : Surabaya is one of the cities with low coverage of exclusive breastfeeding in East Java. The average rate of babies who got exclusive breastfeeding in Surabaya from 2012 to 2015 was 63.13% (target 80%). Decision about whether to breastfeed or not is a challenge for every mother, especially for working mothers. This research aimed to identify breastfeeding behavior among working mothers and housewives.Methods : This was descriptive observational research with prospective cohort study design.The sample size was 79 mothers in the eastern part of Surabaya chosen by purposive sampling technique.Results : Result showed that 56.6% of housewives have low knowledge on breastfeeding. Both working mothers (100%) and housewives (90.6%) already give colostrum right after baby born. However, There were 54.7% of housewives and 46.2% of working mothers already give formula milk during the first month after baby born.Conclusion : There were not much difference between working mothers and housewives in knowledge, feeding colostrum and skin to skin contact aspects. But, working mothers mostly give formula milk during the first month of baby born than housewives.